Actividades turísticas en la ruta del cacao fino de aroma como experiencia vivencial en la Provincia Los Ríos - Carriel Santillán, Lady Mercedes (2021)
The purpose of this research is to publicize the importance of identifying tourist activities on the route of fine aroma cacao as an experiential experience in the province of Los Ríos. In order for farmers and agricultural estates to be beneficiaries through tourism, through the generation of tourist destinations, economic income and the creation of new jobs, which will contribute to the development of the economy in the province of Los Rios. Activities in the agro-tourism sector are increasing every day, essentially in areas where daily agricultural activities predominate, one of these places is the province of Los Rios, which has a large extension of agricultural areas such as the cocoa farms of the province de Los Rios, which have unique characteristics in the rural area, these detail the production and cultivation of fine aroma cocoa along with recreational activities.